Manajemen Konflik dalam Perspektif Islam di Masa New Normal Pandemic Covid-19 - Gladys Dwiani Tinovella Tubarad (Kuras Institute, 2022)
Conflict is a condition that arises from incompatibility or conflict that affects the parties involved, both positive and negative influences. There are two views related to the consequences or effects of conflict. This study aims to look at conflict management in reducing work stress during the COVID-19 pandemic from an Islamic perspective. This research uses the method. This research uses a type of literary research, or library research that relies on a literature review related to the object of research. the proactive model comes from the leadership of the Prophet Muhammad SAW, the SALAM model is seeing, agreeing, learning, learning, and realizing, and the SNT model, namely Shura (deliberation), Naseeha (advice), and Ta'awun (cooperation). The results of the intervention show that the tendency to reduce stress when implementing conflict management is seen from an Islamic perspective during the COVID-19 pandemic.